Center and centralities in focus: A look at Gávea Centro and its centralities in the South Sector of Uberlândia-MG - Alves, Lidiane Aparecida (National Journal of City Management, 2024)
The general objective of this article is to explore the urban dynamics and the different conceptions of center and centrality; The specific objectives are to address the emergence of new centralities and their dialectic in the continuous movement of space production in the city and to highlight centrality as a possibility for improving the quality of urban life. Given its character as a reflexive effort, it is methodologically supported by a bibliography review and a brief approach to the empirical reality of Uberlândia-MG. It does not have the purpose of exhausting the theoretical framework on the subject, but is more of a brief interpellation, an invitation to debate. The text is divided into three parts, in addition to the introduction. Initially, it addresses the conceptualization of city and urban, in order to highlight the constant change in the structure of cities, well understood in the following topic, which addresses the concepts of center and centrality. In the following part, possibilities inherent to centralities are suggested. The last topic, in turn, is discussed based on the theories presented the conjuncture of the Southern Sector of the city of Uberlândia-MG, where will be constituted the Gávea Center with its centralities: Villa Gávea, Park Gávea and Gávea Garden.
Keywords: New centralities planned; Integrated Center; Urban Dynamics; Urban Structure